Characteristics of propolis encapsulated with gelatin and sodium alginate by complex coacervation method - Nandi Sukri; Thalia Tashya Marin Putri; Mahani; Bambang Nurhadi (International Journal of Food Properties)
Propolis is a sticky resin from bees and contains reasonable amounts of bioactive compounds that benefit the human body. Despite the benefits that propolis has to offer, propolis also has a bitter taste and pungent aroma. These characteristics of propolis could be controlled by a microencapsulation process with a complex coacervation method using gelatine and sodium alginate as coating material. The amount of propolis added was also varied in F1 (5 ml), F2 (10 ml), and F3 (15 ml). This study aimed to determine the effect of different concentrations of propolis on the physicochemical characteristic of propolis microcapsule. The results showed that increasing the addition of propolis concentration could also increase yield, total phenolic content, hygroscopicity, and solubility. Meanwhile, the increase in propolis concentration showed a decrease in encapsulation efficiency, moisture content, water activity, and dissolution time. Propolis microcapsules have a round morphology and several hollows on the surface. The best treatment was seen in F1, which obtained microcapsules of propolis with an encapsulation efficiency of 91.86%, and F3 which obtained microcapsules with high spraydried yield and solubility, fast dissolution time, and low value of moisture content, water activity, and hygroscopicity.